Mappings of chemicals distribution in preservatives treated tropical bamboo gigantochloa scortechinii - Razak Wahab; Othman Sulaiman; Aminuddin Mohamed; Mohammed Abdus Salam; Shafiqur Rahman; Mohd Sukhairi Mat Rasat; Hashim W. Samsi (RJPBCS, 2014)
The mappings of chemicals in preservatives treated bamboo Gigantochloa scortechinii were studied. The chemical's distribution in the bamboo indisputably influences their durability against the attacks of the insects and fungi. This largely depends on the chemicals penetration, location and retention at the tissue and cell walls levels in the bamboo. At optimum retention levels, the preservative performance should be comparable unless the preservative's distribution, substrate susceptibility or fixation product had altered. In evaluating the performance of various treatment methods employed, the distribution of preservatives within the cell walls of treated bamboo must be considered. The results from the energy dispersive x-ray analysis on the bamboo treated with Copper Chrome Arsenic, and Ammoniacal Copper Quaternary are analyzed. The G. scortechinii samples were treated by soaking, vacuum pressure impregnating and high-pressure sap-displacement. Observation was carried out using the Transmission Electron Microscope linked system to an energy dispersive x-ray analyzer. The system enables to detect preservative distribution at the cellular level and measured relative preservative content into the lumen surface, in the S2 cell wall layer and in the middle lamella.